Introduction to the Special Issue on GaLA Conf 2022 - Antti Koskinen; Kristian Kiili; Francesca De Rosa; Muhterem Dindar; Michael Kickmeier-Rust (Serious Games Society, 2023)
This International Journal of Serious Games special issue is dedicated to the selected and extended best papers of the 2022 edition of the GALA conference. Professor Kristian Kiili and his team at Tampere University in Finland organized this edition of the conference. Authors of seven highly-rated conference submissions were invited to submit extended papers for this special issue. After peer review process, five extended papers were accepted. These papers shows how game-based learning and serious games continue to evoke extensive research efforts, and clearly demonstrates the breadth of different research approaches used in game-based learning. With such an open-minded approach, it is possible not only to advance our knowledge of game-based learning but also to contribute significantly to the understanding of the factors that influence human learning.